"Na escola sou brasileiro e lá em casa sou árabe": a escola pública iguaçuense nos interstícios das línguas e culturas - Nascimento, Kelin Regina Bergamini do (2023)
The presence of languages in contact in the vicinity of Brazilian public schools clashes with their inner silencing. The difference presents itself as a problem in the Brazilian educational scenario, whose hegemonic monolingualism is still widely practiced. The present study is located on the theme of schools set in specific multilingual contexts. So, this research proposes the case study of the Municipal School Teacher Elenice Milhorança, in the city of Foz do Iguaçu – PR, due to the increased demand for enrollment of Arab students, migrants or descendants, which has been occurring after the closing of the Arab Brazilian College, in 2019, intensifying with the economic and social consequences of the pandemic period. Knowing that approximately 8% of the population of Iguaçu is composed of Arabs and their descendants, the research is justified by the need to integrate students from these communities into municipal public schools and develop strategies or mechanisms to better serve them. Therefore, the question is: “how does the process of sociolinguist interaction of students from Arab communities in Elementary School I, in the context of public education in Foz do Iguaçu?”. From the research question emerges as a central objective: “to investigate the process of sociolinguist interaction of students from communities of Arab descent, in the context of Elementary School I, in the public school system, specifically at the Municipal School Teacher Elenice Milhorança”. As for the epistemological affiliation, it is a research in the area of Applied Linguistics, of a qualitative nature and interdisciplinary profile, starting from Educational Sociolinguistics, under the perspective of the Interpretative Paradigm. As for the methodological route, this case study has exploratory – descriptive purposes. The data generators used were: semistructured interviews with fathers/mothers of Arab students or descendants and the pedagogical team, structured questionnaire applied in the selected class and participant observations recorded in a field diary. The results indicated that migrant students have more difficulties interacting with teachers and classmates, preferring the company of other classmates from Arab ancestry, while descendants are more integrated into the group. It was also, verified, that the language management adopted by the school and its interaction with the families interfere quantitatively and qualitatively in the established links. The research brought as direct implications the evidence of the lack of a specific educational policy for the multilingual/multicultural context in Foz do Iguaçu and the need to encourage new academic studies that make the problem visible, so that its inclusion in the guidelines of public policies in Iguaçu come true.